2021
DOI: 10.1111/cla.12476
|View full text |Cite
|
Sign up to set email alerts
|

Parsimony analysis of phylogenomic datasets (II): evaluation of PAUP*, MEGA and MPBoot

Abstract: This paper examines the implementation of parsimony methods in the programs PAUP*, MEGA and MPBoot, and compares them with TNT. PAUP* implements standard, well-tested algorithms, and flexible search strategies and options for handling trees; its main drawback is the lack of advanced search algorithms, which makes it difficult to find most parsimonious trees for large and complex datasets. In addition, branch-swapping can be much slower than in TNT for datasets with large numbers of taxa, although this is only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…Other studies not addressed by Marjanović & Laurin (2019) have reported different topologies recovered by heuristic TNT and PAUP* ( e.g ., Kurochkin et al, 2011 ; Han et al, 2016 ; Audo, Barriel & Charbonnier, 2021 ), but assessing whether these too might have failed to obtain all MPTs is beyond the scope of this study. A recent comparison of performance of different parsimony programs on phylogenomic data by Goloboff, Catalano & Torres (2021) noted that PAUP* recovered optimal trees in all datasets but one compared to TNT. Other paleontological studies have recovered the same number and length of MPTs between programs, both with large numbers of MPTs ( e.g ., Spaulding, O’Leary & Gatesy, 2009 ; Ford & Benson, 2020 ) and with small numbers of MPTs ( e.g ., Davesne et al, 2016 ; Villalobos-Segura, Underwood & Ward, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies not addressed by Marjanović & Laurin (2019) have reported different topologies recovered by heuristic TNT and PAUP* ( e.g ., Kurochkin et al, 2011 ; Han et al, 2016 ; Audo, Barriel & Charbonnier, 2021 ), but assessing whether these too might have failed to obtain all MPTs is beyond the scope of this study. A recent comparison of performance of different parsimony programs on phylogenomic data by Goloboff, Catalano & Torres (2021) noted that PAUP* recovered optimal trees in all datasets but one compared to TNT. Other paleontological studies have recovered the same number and length of MPTs between programs, both with large numbers of MPTs ( e.g ., Spaulding, O’Leary & Gatesy, 2009 ; Ford & Benson, 2020 ) and with small numbers of MPTs ( e.g ., Davesne et al, 2016 ; Villalobos-Segura, Underwood & Ward, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies not addressed by Marjanović & Laurin (2019) have reported different topologies recovered by heuristic TNT and PAUP* (e.g., Kurochkin et al, 2009;Han et al, 2016;Audo, Barriel & Charbonnier, 2021), but assessing whether these too might have failed to obtain all MPTs is beyond the scope of this study. A recent comparison of performance of different parsimony programs on phylogenomic data by Goloboff, Catalano & Torres (2021) noted that PAUP* recovered optimal trees in all datasets but one compared to TNT. Other paleontological studies have recovered the same number and length of MPTs between programs, both with large numbers of MPTs (e.g., Spaulding, O'Leary & Gatesy, 2009;Ford & Benson, 2020) and with small numbers of MPTs (e.g., Davesne et al, 2016;Villalobos-Segura, Underwood & Ward, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, although they employ different philosophical foundations, S is the ML analogue of other direct measures of support like Goodman-Bremer (GB) and ratio of explanatory power (REP) values in parsimony analysis (Grant & Kluge, 2007, 2010 and posterior odds ratio in Bayesian statistics (Bolstad, 2007;Grant & Kluge, 2008). As such, it also enjoys the advantageous properties of all those measures that have a clear and direct relationship to optimality, in contrast to clade credibility values (often referred to as posterior probabilities) in Bayesian phylogenetics and BS in parsimony, neither of which assesses the strength of evidence for competing hypotheses (Grant & Kluge, 2008; see also Goloboff et al, 2003;Goloboff et al, 2021).…”
Section: Discussionmentioning
confidence: 99%